Ageing and intergenerational relations : family reciprocity from a global perspective - Izuhara, Misa. (Bristol : Policy Press, 2010)
'With socio-economic and demographic changes taking place in contemporary societies, new patterns of family relations are forming partly due to significant family changes, value shifts, precariousness in the labour market, and increasing mobility within and beyond national boundaries. This exciting book explores the exchange of support between generations and examines variations in contemporary practices and rationales in different regions and societies around the world. It draws on theoretical perspectives and empirical analyses to discuss both newly emerging patterns of family reciprocity and more established ones which are affected by changing opportunities and pressures in contemporary societies. The book is split into two parts: the first reviews key theoretical and conceptual debates in this field, while the second offers new insights and an understanding of exchange practices based on case studies from different regions and different relationships.'--Publisher's description.
Introduction / Misa Izuhara -- Globalisation, global ageing and intergenerational change / Chris Phillipson -- Theoretical perspectives on intergenerational solidarity, conflict and ambivalence / Ruth Katz and Ariela Lowenstein -- Globalised transmissions of housing wealth and return migration / Ricky Joseph -- Housing wealth and family reciprocity in East Asia / Misa Izuhara -- Grandparents and HIV and AIDS in Sub-Saharan Africa / Akpovire Oduaran and Choja Oduaran -- Spiritual debts and gendered costs / Pascale F. Engelmajer and Misa Izuhara -- Reciprocity in intergenerational relationships in stepfamilies / Lawrence H. Ganong and Marilyn Coleman -- New patterns of family reciprocity? Policy challenges in ageing societies / Misa Izuhara.
Includes bibliographical references and index.
Keywords: Aging -- Cross-cultural studies; Intergenerational relations -- Cross-cultural studies; Older people -- Social conditions -- Cross-cultural studies